Research on Digital Transformation and Corporate Financial Asset Allocation Strategy - Xie, Yuduo (International Journal of Global Economics and Management, 2024)
The new-generation information technology revolution is profoundly changing the economy and society, and promoting industrial innovation and leapfrogging. China actively promotes the synergistic development of industrial digitization and digital industrialization, which has significantly increased the scale of the digital economy. In this context, the digital transformation of enterprises has become a key issue, and the strategic choice of financial asset allocation, as an important factor affecting the operational performance, investment and financing decisions, and innovation activities of enterprises, has attracted much attention. This study constructs the framework of "financial asset allocation behavior-digital transformation", based on the data of A-share listed companies in Shanghai and Shenzhen from 2012 to 2019, and empirically analyzes it by using the fixed effect and threshold model, and finds that the relationship between the allocation of financial assets and the digital transformation is in an inverted U-shape: moderate allocation and digital transformation have an inverted U-shape relationship. It is found that the relationship between financial asset allocation and digital transformation is "inverted U-shaped": moderate allocation promotes transformation, while excessive inhibits it. Short-term financial assets play the role of "reservoir" and support the transformation, while long-term financial assets may produce crowding-out effect. Financing constraints and financial return thresholds also have differentiated impacts on the relationship. This study provides new perspectives and theoretical support for enterprises to optimize resource allocation and achieve sustainable development.